Answer:
d. -6
Step-by-step explanation:
By the remainder theorem, we get that:
![f(x)=(x+1)\cdot q(x)+r](https://img.qammunity.org/2023/formulas/mathematics/college/rezatc4dhxo1xo49hdcz5dy45d2le1prl9.png)
Where q(x) is another polynomial and r is the remainder.
To eliminate the value of q(x), we will replace x by -1 to get:
![\begin{gathered} f(-1)=(-1+1)\cdot q(-1)+r \\ f(-1)=0\cdot q(x)+r \\ f(-1)=r \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8zfoiwy9uwu0posnjhpojgaitltyf31cha.png)
But f(x) = x^(88) + 5x - 2, so f(-1) will be equal to:
![\begin{gathered} f(x)=x^(88)+5x-2 \\ f(-1)=(-1)^(88)+5(-1)-2 \\ f(-1)=1-5-2 \\ f(-1)=-6_{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fyw80pvqk3u7tbhbxll3ha8ad2f3wz7du8.png)
Therefore, if f(-1) = -6 and f(-1) = r, we get that
r = -6
So, the remainder is d. -6